Secure data transmission for multibiometric identity verification systems using steganography and encryption - Killioglu, Mehmet; Taskiran, Murat; Kahraman, Nihan (PAMUKKALE UNIV, 2018)
Effort on biometric data security in recent years in order to secure the transmission of biometric data along with the spread of biometric systems and can not be seized by any person other than the user is increasing rapidly. In this work, Advanced Encryption Standard (AES) and RSA (Rivest, Shamir, Adleman) algorithms were intended to ensure the security of biometric data using the algorithm. First fingerprint biometric data to be provided as security image is obtained. The noise in background of the resulting fingerprint image has been cleared using morphological operations. Thinning is applied to fingerprint image that background noise is cleared and the secondary feature vectors (minutiae points such as bifurcations and ridge endings) has obtained. The region of interest near the center of the fingerprint image is determined as the area of interest (ROI), the positions of the bifurcation and the ridge endings in this region along the x and y axes, as well as three angles for the bifurcation and one for the ridge endings in feature vectors. Each vector element has converted to 16 bit and then encoded by 128 bits blocks using AES. These encoded bits were embedded to least significant bits of red layer of the thermal image. Which pixels of the thermal image are to be replaced is determined by the information used for addressing in the green layer. In order to to obtain biometric data on the thermal image by the receiver side, the first used AES key was transmitted to the receiving side encrypted with RSA algorithm. Finally, original thermal image and biometric data embedded thermal image using steganography are compared by analyses.
Keywords: Steganography; Fingerprint; Thermal image; Advanced encryption standard (AES); RSA; Engineering